Exploring past experience of becoming a transgender woman: perspective from Malaysian Muslim transgender women: a qualitative study - Said, Abdul Hadi; Mohd, Farah Natashah; Mokhtar@Makhtar, Khairani Idah; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari; Draman, Samsul (Ektodermal Displazi Grubu, 2023)
Abstract Little is known about the factors contributing to become transgender women in a Muslim country. Thus, this study aims to explore the past experience and factors contributed to become transgender among transgender women. Transgender women in Kuantan, Pahang were invited to participate in an audiotaped in-depth interviews in 2021, conducted in Malay using a topic guide. The qualitative data were recorded, transcribed and analysed using framework analysis. Majority of the respondents (n=8) admitted they have the tendency of becoming females since childhood. Some were being treated as females and they grew up with strong perceptions that they should be female. They found their circles of transgender women later in their life when they were not supported by family members. Most of the respondents agreed that they work as sex workers because of their own desire and had history of being discriminated at work.